Phenomenon of Good in Perspective of Hospice Care - Chrząstowska, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
An aim of this article is to depict a phenomenon of good, understood as a ethical attitude tied with specific psychological after-effects, in caring on dying people. As it is shown, the good itself lies both on basics of modern hospice movement, as well as in daily practice of first hospice that realizes its goals – that is St Christopher’s Hospice in London, which is an exemplar and source of inspiration for many others established in whole World.